The Relevance of Campus Transportation Shuttle to The Realization of Green Economy and Conservation of Universitas Negeri Semarang - Sari, Mayiswa Fatika; Al-Hanif, Ervando Tommy; Wicaksana, Muhammad Guruh Bintang; Nurcahyono, Tatok; Berliana, Arla Janitra; Sabikoh, Okti Kamelia (P4W IPB, 2025)
The green economy program aims to boost the economy while preserving nature. UNNES has been implementing a green economy program through conservation activities campus transportation shuttle facilities since August 10th, 2022. The research aims to know the the academic community and shuttle manager perception regarding the relevance of the shuttle to the realization of the green economy and UNNES conservation, to know the perceptions of environmental experts and educators about green economy of UNNES, and to know the the relevance of campus transportation shuttles to the green economy and UNNES Conservation. The research method uses library studies, field surveys, observations, and interviews with descriptive analysis and regression. Results of the research obtained an interrelation coefficient of 0.759 means shuttle has a high relevance in realizing the green economy and conservation UNNES programs. On Monday there were 3.4 rhythms, on Wednesday 3.8, and Friday 3.9. The efficiency on Monday was classified as moderate, Wednesday and Friday as high. BBM consumption cost calculation results show that electric vehicles require costs of Rp33.980/100 km, more economical than motor vehicles and conventional cars with costs of Rp35.000/100 km and Rp107.600/100 km. Conclusion, the shuttle has high relevance and high relevance toward UNNES Conservation and green economy based on academics and shuttle manager, UNNES already implementing the concept of a green economy, but it still needs to be improved.